Pesticide use in Thailand: Current situation, health risks, and gaps in research and policy - Wisanti Laohaudomchok (2020)
© 2020 Taylor & Francis Group, LLC. Agriculture in Thailand, which employs over 30 percent of the workforce and contributes significantly to the country’s gross domestic product, is a key sector of its economy. Import and use of pesticides has increased over the past decade due to Thailand's major role as a leading exporter of food and agricultural products. The widespread and poorly regulated use of pesticides presents a potential risk to the health of farmers, farm families, the general population including children and the environment. This article is a result of the Southeast Asia GEOHealth Network Meeting of February 2019. It summarizes the current situation on pesticide use and regulation in Thailand and reports research findings on the potential health and environmental impacts of pesticide use, as well as highlighting gaps in research that could play an important and influential role in future policy initiatives on pesticides. Although Thailand has made remarkable progress in improving agricultural health and safety and similarly strong research and policy programs are being developed in other countries in the region, there are still significant gaps in research and policy that need to be filled.